Mechanochemical Synthesis and Characterization of Samarium Oxide-Hematite Magnetic Ceramic Nanostructures - Sorescu, Monica; Adams, Lona; Tolea, Felicia; Sofronie, Mihaela; Kelly, Jordan C; Aitken, Jennifer A (European Journal of Applied Sciences, 2024)
Mixed-oxide nanostructures of the type xSm2O3-(1-x)alpha-Fe2O3 (x=0.1 and 0.5) were synthesized by mechanochemical activation for ball milling times of 0, 2, 4, 8 and 12 hours. The 0-h Mӧssbauer spectrum was analyzed with a sextet characteristic to hematite. A second sextet with a lower value of the hyperfine magnetic field was assigned to samarium-doped hematite. An additional quadrupole-split doublet, whose abundance showed a general trend to increase with the ball milling time, was attributed to superparamagnetic samarium iron perovskite (samarium orthoferrite) phase. The X-ray diffraction (XRD) patterns for the equimolar composition were dominated by the diffraction peaks of SmFeO3 after 12 h of milling. The hysteresis loops recorded at 5 K and an applied magnetic field of 5 T exhibited higher values of the magnetization than the similar ones measured at 300 K, but did not saturate at this field strength. The coercive field values showed a decrease with decreasing the particle size after prolonged milling. The zero-field-cooling-field-cooling (ZFC-FC) measurements performed at 200 Oe and 5-300 K were consistent with an increase in magnetization with ball milling time. The Tauc plots derived from the optical diffuse reflectance spectra showed that the samples were semiconductors with a band gap of 2.1 eV.